Evaluation of Some Synthesized Novel Substituted Phthalimide Derivatives as Potent Antidiabetic Agents - Mahapatra, Shankhapani; Singh, Jagadish; Raju, Rajapandi; Charan Maiti, Bhim; Kumar Maity, Tapan (Asian Journal of Chemistry, 2010)
Tetrachlorophthalimide derivatives were synthesized and their ability to inhibit a-glucosidase was investigated in vitro as well as in vivo in streptozotocin-induced diabetic rats. The purity of synthesized compounds were confirmed by spectral and elemental analysis. Then the compounds were biologically screened on streptozotocin-induced diabetic rats compared with standard drug (miglitol). Tetrachlorophthalimide derivatives were potent inhibitors of yeast a-glucosidase (IC50 at 50 μM). Administration of S-5, S-2 and SE-II-13 orally at the dose of 250 mg/kg body weight resulted in significant (p < 0.001) reduction in blood glucose levels. The body weights were significantly (p < 0.001) reduced in streptozotocin-induced diabetic rats when compared to normal rats. The present study reveals that out of all synthesized compounds, N-(2,4-dinitrophenyl) tetrachlorophthalimide could be a representative of a new group of a-glucosidase inhibitors and exhibit significant anti-hyperglycemic effect.